Treatment Of Schizophrenia With Cobenfy (KarXT): A Literature Review - Kurczoba, Laura; Skonieczna, Karolina; Badziąg, Magdalena; Szulc, Paulina; Kłossowska, Martyna; Wiciun , Olimpia; Kądziołka, Olga; Ordon, Kacper (Quality in Sport, 2025)
Introduction and purpose: In September 2024, the FDA approved a new drug for the treatment of schizophrenia in adults, Cobenfy, also known as KarXT. COBENFY combines xanomeline, a muscarinic agonist, and trospium chloride, a muscarinic antagonist. It is the first antipsychotic approved for the treatment of schizophrenia that targets cholinergic receptors rather than dopamine receptors, which could be a completely new standard of care. The purpose of this literature review is to introduce the new psychotropic drug, discuss the mechanism of action, and present the results of the EMERGENT-1, EMERGENT-2 and EMERGENT-3 clinical trials. Materials and methods: The authors conducted an extensive review of articles available in PubMed and Google Scholar. Standard criteria were used to review the literature data. The search of articles in the database was carried out using the following keywords: schizophrenia, dopamine hypothesis, cholinergic hypothesis, xanomeline, trospium. Conclusions: EMERGENT-2 and EMERGENT-3 trials have shown significant improvement in positive and negative symptoms of schizophrenia. Cobenfy may be a good alternative in the management of schizophrenia, especially in resistant cases to conventional therapy or intolerable side effects to conventional therapy. However, to evaluate the long-term safety, tolerability, and efficacy of KarXT there is a need to analyze longer studies whose ongoing research are unpublished yet.